2010
DOI: 10.1021/bm9010722
|View full text |Cite
|
Sign up to set email alerts
|

Lung Perfusion Imaging with Monosized Biodegradable Microspheres

Abstract: After intravenous injection, particles larger than red blood cells will be trapped in the first capillary bed that they encounter. This is the principle of lung perfusion imaging in nuclear medicine, where macroaggregated albumin (MAA) is radiolabeled with (99m)Tc, infused into a patient's arm vein, and then imaged with gamma scintigraphy. Our aim was to evaluate if monosized microspheres could replace (99m)Tc-MAA. Biodegradable poly(L-lactide) microspheres containing chelating bis(picolylamine) end groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…Therefore, the majority of animal studies using this technique have focused on large species (Bajc et al, 2002;Kozian et al, 2008). SPECT with pinhole collimation has enabled lung perfusion studies in mice (Hä feli et al, 2010). During recent years, other imaging techniques have been used to image regional lung blood flow and ventilation, some of which are described next.…”
Section: Imaging In Respiratory Diseases: From Animal Models To Patientsmentioning
confidence: 99%
“…Therefore, the majority of animal studies using this technique have focused on large species (Bajc et al, 2002;Kozian et al, 2008). SPECT with pinhole collimation has enabled lung perfusion studies in mice (Hä feli et al, 2010). During recent years, other imaging techniques have been used to image regional lung blood flow and ventilation, some of which are described next.…”
Section: Imaging In Respiratory Diseases: From Animal Models To Patientsmentioning
confidence: 99%
“…Furthermore, other advantages of the flow focusing method include the variation in fluid and gas phases that potentially allow minimizing the stress that is applied during the particle generation procedure. This will allow the encapsulation of labile compounds and is part of a larger investigation [1]. Further advantages include the achievement of different morphologies, surface treatments and compositions that can be achieved (e.g., two-phase capsules or hollow capsules); and that high particle production rates could be achieved after scaling the flow focusing geometries into two-dimensional arrays.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the successful preparation of biodegradable drug loaded particles for drug delivery studies with diameters on the order of 8-10 m [1,25]. Here we investigate the potential of flow focusing for the preparation of biodegradable microspheres, with diameters below 5 m. Particles of such a small size will improve the drug delivery when compared to larger particles as a result of better distribution in small blood capillaries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the problem of sedimentation, several strategies have been proposed (e.g., the addition of thixotropic agents, surfactants, and nanoparticles; the use of viscoplastic media as carriers; and polymeric core/shellstructured magnetic particles) 23 . The sedimentation problem in MRFs is of such importance that it has even been investigated (together with other properties) under microgravity conditions in outer space 24 . A very recent study reports on the rheological behaviour of suspensions of hematite nanoparticles in an IL 25 .…”
Section: Introductionmentioning
confidence: 99%